2021
DOI: 10.3390/ma14247883
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pin Shape on Thermal History of Aluminum-Steel Friction Stir Welded Joint: Computational Fluid Dynamic Modeling and Validation

Abstract: This article studied the effects of pin angle on heat generation and temperature distribution during friction stir welding (FSW) of AA1100 aluminum alloy and St-14 low carbon steel. A validated computational fluid dynamics (CFD) model was implemented to simulate the FSW process. Scanning electron microscopy (SEM) was employed in order to investigate internal materials’ flow. Simulation results revealed that the mechanical work on the joint line increased with the pin angle and larger stir zone forms. The simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 77 publications
(73 reference statements)
0
15
0
Order By: Relevance
“…In general, in the FSW of dissimilar materials, the portion of participation of materials determines the joint properties [ 42 , 43 ]. Imbalance in the volume ratio of plastic flow leads to inappropriate material mixing at weld nugget and finally increment in defects density [ 44 , 45 , 46 ]. The tool offset in the dissimilar joint is an essential issue because it increases FSW tool life and base metal mixing.…”
Section: Resultsmentioning
confidence: 99%
“…In general, in the FSW of dissimilar materials, the portion of participation of materials determines the joint properties [ 42 , 43 ]. Imbalance in the volume ratio of plastic flow leads to inappropriate material mixing at weld nugget and finally increment in defects density [ 44 , 45 , 46 ]. The tool offset in the dissimilar joint is an essential issue because it increases FSW tool life and base metal mixing.…”
Section: Resultsmentioning
confidence: 99%
“…At the bottom surface, the local temperature governed the heat transfer coefficient according to the following equation [43]:…”
Section: Heat Transfer Modelmentioning
confidence: 99%
“…Based on Figure 8, it was found that increasing plunge depth led to a significant increase in the maximum temperature of the FSW process. In general, friction and plastic flow created in the FSW process result in heat generation in the weld zone [57,58]. Generated heat produced by the aforementioned factors significantly changes with plunge depth.…”
Section: Plunge Depth Effectmentioning
confidence: 99%